Optimization of plant growth regulators for Citrus suhuiensis callus induction - M. Fathil, Nur Alia; Mohamad Puad, Noor Illi; Amid, Azura; Azmi, Azlin Suhaida; Ibrahim, Rusli (Malaysian Society for Molecular Biology and Biotechnology, 2017)
Correct types and concentration of plant growth regulators (PGRs) will enhance and optimize the growth of callus cultures. This paper reported the effects of several types of cytokinins (2,4-dichlorophenoxyacetic acid (2,4-D) and 1-naphthalene acetic acid (NAA)) and auxins (6–Benzylaminopurine (BAP) and kinetin) on the callus induction of C. suhuiensis. The cotyledons from C. suhuiensis seeds were excised as the explant and cultured on Murashige and Skoog (MS) media, 3% (w/v) sugar, 0.05% (w/v) malt extract and 0.25% (w/v) agar under the continuous dark condition supplemented with the chosen PGRs at the concentration range of 0.5, 1.0, 2.0, 3.0 and 4.0 mg/L. The growth of callus at each treatment was measured as gram (g) of fresh weight and percentage of callus induction. The results showed that 1.0 mg/L 2,4-D gave the highest growth of callus (0.15 g and 100% callus percentage). After identifying the effective PGRs, Central Composite Design (CCD) from the Design Expert® software version 9.0 was used to obtain the optimum concentration of cytokinin and auxin on C. suhuiensis callus cultures. It was observed that the highest amount of callus culture induced was 0.218 g when the media was supplemented with 1.0 mg/L 2,4-D and 1.0 mg/L kinetin.